INTERSPINOUS SPACER IN PERSISTENT DISCOGENIC PAIN: PERCUTANEOUS APPROACH OR OPEN TECHNIQUE - José Antonio Cruz Ricardez; Jesús Alfonso Cao Romero Arroyo (Coluna/Columna)
ABSTRACT Objective: To compare the postoperative clinical course of placement of interspinous spacer with open technique (ISO) with percutaneous interspinous spacer (PIS). Methods: Quasi-experimental, longitudinal study of 42 patients with discogenic pain uncontrolled with analgesics, aged 35-55 years old, 21 women, and 21 men. Clinical history, location of pain, VAS scale before and after surgery, Oswestry Disability Index and Macnab modified scale at 6 months were used. Results: When performing quantitative analysis statistical significance (p = 0.0478, 0.0466, 0.0399) was demonstrated with Student's t test between the results according to VAS scale; in the qualitative analysis with the Oswestry index and Macnab modified scale it was demonstrated the hypothesis that the results is dependent of the surgical technique. Conclusions: According to the results, we can conclude that there is a statistically significant difference depending on the surgical technique used with respect to the rate of disability and functionality in daily life as well as in the improvement of pain symptoms.